Effects and Underlying Mechanisms of Bioactive Compounds on Type 2 Diabetes Mellitus and Alzheimer's Disease. (17th January 2019) - Li, Rongzi; Zhang, Yuxian; Rasool, Suhail; Geetha, Thangiah; Babu, Jeganathan Ramesh
Abstract : Type 2 diabetes mellitus is a complicated metabolic disorder characterized by hyperglycemia and glucose intolerance. Alzheimer's disease is a progressive brain disorder characterized by a chronic loss of cognitive and behavioral function. Considering the shared characteristics of both diseases, common therapeutic and preventive agents may be effective. Bioactive compounds such as polyphenols, vitamins, and carotenoids found in vegetables and fruits can have antioxidant and anti-inflammatory effects. These effects make them suitable candidates for the prevention or treatment of diabetes and Alzheimer's disease. Increasing evidence from cell or animal models suggest that bioactive compounds may have direct effects on decreasing hyperglycemia, enhancing insulin secretion, and preventing formation of amyloid plaques. The possible underlying molecular mechanisms are described in this review. More studies are needed to establish the clinical effects of bioactive compounds.